2008
DOI: 10.1039/b806285d
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalysed anomalous dimerization of styrenes involving the cleavage of the ortho C–H bond

Abstract: The dimerization of styrene derivatives in the presence of a rhodium catalyst proceeds to give stilbene derivatives, in which the ortho C-H bond of styrenes is cleaved and functionalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…To bisu and co-workersw eret he first to report the rhodium-catalyzed dimerization of styrenes involving ortho-CÀHb ond cleavage. [18] In contrast to the conventional head-to-tail, tail-to-tail, or head-to-head dimers, they observed the unusual dimerization product 7 in moderate yields after reactingv arious styrenes in the presence of 10 Twop ossible mechanisms are considered for this reaction (Scheme 9). [18] In path A, the reaction is initiated by the coordination of styrene to the rhodium centert of orm p-complex C1,w hichu ndergoes oxidative cyclization to give intermediate C2 and ac onsecutive 1,2-hydride shift to give rhodium(III) hydride complex C3.I nsertion of the second styrene molecule into the RhÀCb ond, followed by intramolecular hydrometalation, gives C5.S equential b-hydride elimination and reductive elimination gives 7 and regenerates the rhodium(I) species.…”
Section: Rhodium-catalyzed Dimerization Of Styrenes Involving Ortho-cmentioning
confidence: 98%
“…To bisu and co-workersw eret he first to report the rhodium-catalyzed dimerization of styrenes involving ortho-CÀHb ond cleavage. [18] In contrast to the conventional head-to-tail, tail-to-tail, or head-to-head dimers, they observed the unusual dimerization product 7 in moderate yields after reactingv arious styrenes in the presence of 10 Twop ossible mechanisms are considered for this reaction (Scheme 9). [18] In path A, the reaction is initiated by the coordination of styrene to the rhodium centert of orm p-complex C1,w hichu ndergoes oxidative cyclization to give intermediate C2 and ac onsecutive 1,2-hydride shift to give rhodium(III) hydride complex C3.I nsertion of the second styrene molecule into the RhÀCb ond, followed by intramolecular hydrometalation, gives C5.S equential b-hydride elimination and reductive elimination gives 7 and regenerates the rhodium(I) species.…”
Section: Rhodium-catalyzed Dimerization Of Styrenes Involving Ortho-cmentioning
confidence: 98%
“…In accord with this line, Tobisu and Chatani reported that styrene derivatives underwent rhodium-catalyzed homo-alkenylation of orthoposition with the hydration of a directing alkenyl group to give dimerization products (Scheme 3). 11 These authors proposed that the catalytic reaction starts with the oxidative cyclization of the π-Rh complex to which both vinyl CC bond and ortho-ipsoaryl carbons participate to form a rhodacycle. We have demonstrated that an alkynoxy group (OC¸C) behaves as an electron-deficient alkynyl group and thus is a highly reactive directing group for a palladium catalyst.…”
Section: C-c Bond Formation Reactionmentioning
confidence: 99%
“…In contrast, weakly coordinating π‐directing groups, such as CC bonds, have rarely been utilized, and in particular, the ortho ‐selective CH functionalization of styrenes remains a challenge 3. 4…”
Section: Methodsmentioning
confidence: 99%